2018
DOI: 10.1021/acs.macromol.8b02234
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Preparation of Initiator Layers for Surface-Initiated ATRP: Large-Scale Formation of Polymer Brushes Is Not a Dream

Abstract: We demonstrated for the first time a facile and reproducible preparation of large-scale (∼40 m2) initiator layers for surface-initiated atom transfer radical polymerization (SI-ATRP) using a simple sol–gel solution of (p-chloromethyl)­phenyl­trimethoxysilane and tetraethoxysilane. Highly smooth and transparent initiator layers could be formed on various inorganic/organic substrates via a spin-, wire-bar-, or roll-to-roll-coating without any marked change in surface morphology or bulk properties at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 34 publications
4
61
0
Order By: Relevance
“…Previously reported oxygen-tolerant SI-ATRP processes have involved the application of reducing agents, which simultaneously consume oxygen and generate catalytically active Cu Ibased species. [6][7][8][9][10][11][12] Photo-active compounds were also recently applied as oxygen scavengers and polymerization catalysts for metal-free SI-ATRP, enabling the synthesis of microstructured brushes under ambient conditions, with excellent temporal and spatial control. 13 An alternative, highly efficient approach to circumventing the need for deoxygenation relies on the use of zerovalent copper, Cu 0 , which acts as a source of active catalyst, 14,15 simultaneously consuming dissolved oxygen when the polymerization mixture is not directly exposed to air.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported oxygen-tolerant SI-ATRP processes have involved the application of reducing agents, which simultaneously consume oxygen and generate catalytically active Cu Ibased species. [6][7][8][9][10][11][12] Photo-active compounds were also recently applied as oxygen scavengers and polymerization catalysts for metal-free SI-ATRP, enabling the synthesis of microstructured brushes under ambient conditions, with excellent temporal and spatial control. 13 An alternative, highly efficient approach to circumventing the need for deoxygenation relies on the use of zerovalent copper, Cu 0 , which acts as a source of active catalyst, 14,15 simultaneously consuming dissolved oxygen when the polymerization mixture is not directly exposed to air.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, by exploiting activators regenerated by electron transfer (ARGET) ATRP, various waterborne monomers could be successfully polymerized from large polymeric films in the presence of oxygen, 31 while the application of photocatalysts in light-mediated, metal-free SI-ATRP enabled the fabrication of micropatterned brushes over entire silicon wafers, with high resolution and without the need for deoxygenation of reaction mixtures. 30 Apart from the use of organic "additives" to improve the tolerance of SI-ATRP towards oxygen, Jordan et al demonstrated that Cu 0 -coated plates placed upon initiator-bearing substrates within polymerization mixtures could efficiently act as sources of catalyst, 32 simultaneously consuming oxygen 33 and triggering the rapid growth of a variety of compositionally different brushes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the paint-on method represents the most relevant process industrially, where large surfaces with different geometries may be polymer brush-functionalized. Furthermore, in a recent study by Sato et al, they demonstrated a roll-to-roll coating method using a low-concentration sol–gel solution to functionalize large poly(ethylene terephthalate) (PET) films (0.4 × 100 m 2 ) with an ATRP initiator, at a coating speed of 5 m min −1 ( Figure 3 B) [ 54 ]. Subsequently, “paint-on”-ATRP was demonstrated by spreading a 0.02 mL cm -2 polymerization solution on 40 × 40 cm 2 initiator-functionalized PET films, with another film placed on top, in a sandwich structure.…”
Section: Progress In Synthesis Of Polymer Brushesmentioning
confidence: 99%
“…Copyright 2019 Elsevier. ( B ) Illustration of a roll-to-roll coating process on poly(ethylene terephthalate) (PET) film, reprinted with permission from Sato et al [ 54 ]. copyright 2018 ACS.…”
Section: Figurementioning
confidence: 99%